Analyzing cognitive and affective responses in virtual reality tourism with a special focus on mosque visits among generation Y - Mat Desa, Sıtı Nuur Hamızah; Md Sawari, Siti Salwa; Hussin, Siti Rahayu (KSTCL Press, 2024)
Purpose: To determine Generation Y’s cognitive and affective responses to virtual reality mosque tourism.